KOMPAKTIFIKASI ð’…ð‘ºðŸ’Ã—ð‘ºðŸ MENGGUNAKAN LAGRANGIAN MEDAN SKALAR DENGAN SUKU KINETIK POWER LAW - Putra, Fima Ardianto (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Compactification of 5-D extradimension using Power Law has been successfull in compactifying one extradimension, and obtainning itâ€™s radius and stability information. Nevertheless, from this study, we obtained Anti-de Sitter (AdS) in four dimensional viewpoint. This confirms that the Lagrangian model which are choosen has not yet been compatible with respect to the Lagrangian of our space where we are. Kata Kunci: Campactification, Power Law, dan Anti-de Sitter (AdS).